Transport of Nitrate and Its Fate in an Unconfined Sandy Aquifer of Gareh-Bygon Plain, Islamic Republic of Iran - Mohammadnia, Mehrdad (2007)
In response to the growing awareness of groundwater and surface water degradation, there has been increased concern about NO3ˉ mobility and retention in soils. Artificial recharge of groundwater (ARG) through floodwater spreading systems (FWSS) is conducted in the Gareh-Bygon Plain (GBP), south east of Iran, to facilitate both drinking and irrigating water for desert dwellers. However, floodwater used for ARG, contains 60.30 mg L-1 NO3ˉ on average and may contaminate groundwater. The main objective of this study was to identify the most suitable place for extracting safe drinking water supply in the GBP. Identifying natural sources and main flow pathways of NO3ˉ, impacts of different landuse on the groundwater NO3ˉ concentration, removal processes of NO3ˉ, and predicting NO3ˉ transport using suitable computer model, were specific objectives of this study.